Aloe-Polysaccharides Thin Film As All-Natural And Flexible Resistive Random Access Memory - Yeap, Kee Leong (Universiti Sains Malaysia, 2018)
Electronic-waste (e-waste) is an issue that can pose a threat to the environment and human health. This is because e-waste is not easily to decompose within short term period and it often contains toxic materials such as lead, mercury, beryllium and polyvinyl chloride. Hence, an idea of using Aloe-polysaccharides thin film based resistive random access memory (RAM) is suggested in this research work. In this research, Acemannan powder was used to form Aloe-polysaccharides thin film by mixing with deionized water. Acemannan is the major component in the parenchyma cell of Aloe vera. It is the polysaccharide formed through the linking of mannose (C6H12O6) by β-(1, 4)-glycosidic bonds. Then, the effect of Acemannan powder in the range of 1 mg, 3 mg, 5 mg, 7 mg and the effect of different drying temperatures (40oC, 80oC, 120oC and 140oC) on the memory-switching characteristics of Aloe-polysaccharide thin film based memory device was studied. There was several characterization techniques used to examine the characteristics of Acemannan thin film in term of its chemical, and structural properties. While, Aloe-polysaccharides thin film based memory device was fabricated by mixing Acemannan powder with deionized water to form precursor solution, then spin-coating the solution on top of the Indium tin oxide (ITO)-coated glass substrate with 1000 rpm for 30 seconds. After that, spin-coated sample was dried in oven for 1 hour to form Aloe-polysaccharides thin film. Finally, aluminium was thermally coated on top of the Aloe-polysaccharides thin film using thermal evaporator and characterized using Semicoductor Parameter Analyzer under 1-12 V for forward and reverse bias. Based on the results, 3 mg and 5 mg Acemannan powders showed the most significant change of current density (∆J) at 3 V, 5 V and 9 V for 80oC and 120oC respectively. For 3 mg Acemannan powder, ∆J at 3 V, 5 V and 9 V for forward and reverse bias were 2.040 x 10-4J, 1.860 x 10-4J, 1.727 x 10-4J and 2.361 x 10-4J, 2.059 x 10-4J, 2.011 x 10-4J. While, the ∆J in 5 mg Acemannan powder at 3 V, 5 V and 9 V for forward and reverse bias were 1.850 x 10-4J, 2.171 x 10-4J, 2.216 x 10-4J and 2.011 x 10-4J, 2.348 x 10-4J, 2.406 x 10-4J. This is because 3 mg and 5 mg of Acemannan powder is the suitable amounts to form more trap centers at 80oC and 120oC in the interstitial space of Acemannan thin film which allow the injection electrons to move from top electrode (Al) to bottom electrode (ITO) or vice versa for completing the circuit. Hence, a significant current density can be obtained and set the memory device into ON-state. A suitable sweep voltage of 3V, 5V and 9V is also needed for the electrons to come across and able to be trapped in the trap centers of Acemannan thin film.